Analysis of Service Quality on Customer Satisfaction for Tokopedia Online Marketplace in East Lombok: Analisis Kualitas Pelayanan Terhadap Kepuasan Pelanggan Tokopedia Online Marketplace Lombok Timur - Dwi Risa Meina Wangi; Hilmiati, Hilmiati; Rusminah, Rusminah (International Journal of Management Science, 2023)
This study aims to determine the effect of service quality on customer satisfaction in making purchases at the Tokopedia market place. This study aims to determine the effect of service quality on customer satisfaction in making purchases at the Tokopedia market place. This type of research uses associative research with a quantitative approach. The data collection method used is a sample survey method with data collected directly from respondents using a questionnaire. The population in this study were 100 consumers who had shopped at Tokopedia. The analysis tool used is Simple Linear Regression using SPSS version 25. The results showed that the R2 value was found to be 0.721 (72.1%) which indicates that the effect of the independent variable (quality of service) is .721% while 27.9% influenced by other variables. The results of the t test found that t count > t table on the service quality variable, namely 15.925 > 1.661. Thus the results of the study indicate that the influence of service quality has a positive and significant effect on consumer satisfaction at the Tokopedia market place.